Practice and reflection of sitting Taijiquan on college students' physical and mental adjustment - Zhu, Hongbo; Du, Xiaohong; Du, Chengfeng; Deng, Yuting; Pang, Bo (The Journal of the International Society of Chinese Health Practices, 2021)
Taijiquan contains ancient guidance, Traditional Chinese medicine Yin and Yang, meridians and other classical knowledge of health, emphasizing the "unity of nature and man" and "both inside and outside". Since the reform and opening up, China's economic development is changing with each passing day. With the rapid economic development, people's material level has also been improved by leaps and bounds. People have gradually changed from solving the problem of food and clothing to the present well-off life. In 1989, the World Health Organization further defined health as: health not only refers to the absence of physical diseases, but also includes physical health, mental health, good social adaptation and moral health. College students, a large and vulnerable group, have their own many special problems, such as adapting to the new study and living environment, interpersonal relationship and love problems, as well as the problem of career choice and so on. Whether based on the "talent power" strategy, or from the care of the youth group, the whole society needs to quickly help college students to find a way to relieve psychological pressure and promote mental health. Objective: Studies have found that tai Chi can improve the nervous system, enhance human function, prevent osteoporosis, and most importantly, promote the development of personality and mental health of practitioners. Seated Taijiquan, also known as wheelchair Taijiquan, was created by Professor Guo Zibin. Based on the essence of Taijiquan, continuous innovation and adaptation have formed the famous 13-style seated Taijiquan, which is popular among the elderly or those who have been sitting all year round. However, due to the deviation in cultural propaganda and objectives, the promotion of seated tai Chi among other groups is very slow, which leads to the failure to make the value and function of seated Tai Chi known to more people. On the other hand, an unhealthy behavior of college students is developing very rapidly. That is, in the era of mobile Internet, most college students show lazy behavior, which is not only reflected in classroom learning, but also in physical exercise and social life. Some people are hungry for takeout food, and others eat and drink in their dormitory. This inertia psychology and behavior is a product of the era background, but there is no research finds the eradication of the psychological, so the use of inert psychological dig practicing tai chi chuan on college students' physical and mental exercise the functions and value is very necessary, compared to traditional stand of tai chi chuan, practicing tai chi can make college students will focus on their physical and mental feeling. At the same time, it can relieve the fatigue of the legs, so as to meet the needs of college students to exercise, and to a certain extent in line with the "inertia" psychology of college students. Results: Based on the problems of mental and physical sub-health caused by inert psychology of college students, this paper adopts the methods of literature, questionnaire, logical analysis and experiment to further study the seated taijiquan and college students' mental health. The results of the questionnaire show that the physical and mental health of the current college students is not ideal. The existing status quo includes: the decline of students' physical quality, the feeling of physical weakness, mental anxiety, loneliness and depression. Based on the present situation, this paper analyzes the feasibility of practicing seated taijiquan for college students: it is easy to learn, easy to practice and not easy to fatigue, flexible in time and space, abundant theoretical system and practical cases, and the recognition and learning of college teachers. In the experiment, 13-style sitting Tai Chi was used for intervention treatment of college students. In the implementation of the experimental group, the 13-style Tai Chi was taught by tai Chi teachers with more than 15 years of experience. In terms of teaching strategies, the standardization of movements and shapes was emphasized, and the requirements of tai chi movements in the center of gravity were emphasized. And let the students participate in the experiment as much as possible to feel the different physical and mental feelings brought by the seated tai Chi. Results: After the intervention, the mood of the subjects was greatly improved, the symptoms of anxiety and depression were greatly alleviated, the number of insomnia was reduced or even no, the inner self perception was strengthened, and they began to pay attention to physical and mental health, love tai Chi and other sports. Conclusion: Taijiquan attaches importance to regulating breath and heart, and abdominal breathing can effectively relieve the tension of sympathetic nervous system, improve the mood of college students, so as to realize the effect of strengthening the essence, nourishing the mind and calming the mind, and coordinating Yin and Yang. The most commonly used technique in the sitting exercise of Tai Chi is the rotation of the arms, which helps to stimulate the meridians such as the heart meridian, the pericardium meridian and the lung meridian, and can adjust the three jiao of the human body. Although the seated taijiquan weakens the use of lower limbs, it still requires practitioners to do the waist turning hip tone, so as to enhance the stimulation of the nerves, bones, muscles and joints of the buttocks and waist, promote the muscles and bones strong, flexible joints, and achieve the goal of improving physical quality. Suggestions: The government should strengthen the research and development of seated taijiquan sets, set up associations to promote seated taijiquan in universities, establish a platform for exchange of seated taijiquan, carry out seated Taijiquan competitions, and strengthen the construction of teaching staff.